2020
DOI: 10.1101/2020.11.01.363101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IceR improves proteome coverage and data completeness in global and single-cell proteomics

Abstract: Label-free proteomics by data-dependent acquisition (DDA) enables the unbiased quantification of thousands of proteins, however it notoriously suffers from high rates of missing values, thus prohibiting consistent protein quantification across large sample cohorts. To solve this, we here present IceR, an efficient and user-friendly quantification workflow that combines high identification rates of DDA with low missing value rates similar to DIA. Specifically, IceR uses ion current information in DDA data for a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Approaches for peptide sequence identification offer a tradeoff between sensitivity and specificity. Approaches using extracted ion current, such as IceR, 22 are likely to offer higher sensitivity of peptide sequence propagation. In contrast, approaches using more features, such as DART-ID, 21 are likely to offer higher reliability of peptide sequence identification.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches for peptide sequence identification offer a tradeoff between sensitivity and specificity. Approaches using extracted ion current, such as IceR, 22 are likely to offer higher sensitivity of peptide sequence propagation. In contrast, approaches using more features, such as DART-ID, 21 are likely to offer higher reliability of peptide sequence identification.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been developed to reduce this bias by propagating spectrum identifications from one sample to the corresponding MS1 peaks from another sample. The match between run algorithm of MaxQuant is very popular in label-free SCP [10,9,7,8,34,12], but methodological improvements have recently been suggested for both label-free and TMT-based SCP [35,36]. Finally, another reason for missingness is the inability to match a spectrum to a peptide sequence due to poor spectrum quality.…”
Section: Data Missingnessmentioning
confidence: 99%
“…Several approaches have been developed to reduce this bias by propagating spectrum identifications from one sample to the corresponding MS1 peaks from another sample. The match between run algorithm of MaxQuant is very popular in label-free SCP [10, 9, 7, 8, 34, 12], but methodological improvements have recently been suggested for both label-free and TMT-based SCP [35, 36]. Finally, another reason for missingness is the inability to match a spectrum to a peptide sequence due to poor spectrum quality.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Several approaches have been developed to reduce this bias by propagating spectrum identications from one sample to MS1 peaks from another sample. The match between run algorithm of MaxQuant (Tyanova et al (2016)) is very popular in label-free SCP (Zhu et al (2018a), Zhu et al (2018b), , Cong et al (2020), Cong et al (2021), Brunner et al (2020), but methodological improvements have recently been suggested for both label-free (Kalxdorf et al (2020)) and TMTbased SCP (Yu et al (2020)). Finally, another reason for missingness is the inability to match a spectrum to a peptide sequence.…”
mentioning
confidence: 99%